(untitled) (IAHS Medical Journal, 2023)
Background: Stroke is a leading cause of death and disability in developing countries, afflicting individuals at a young age. The affection of economically productive group adds further to the overall disease burden. The contribution of established vascular risk factors to ischaemic stroke in young adults has not been evaluated systematically in CMH, Dhaka Cantonment. The purpose of the study is to detect the risk factors for acute Ischaemic stroke in adults. Materials and methods: The case-control study was carried out in the department of Neurology and Medicine, CMH Dhaka during October 2019 to August 2020. Consecutive ischemic stroke patients who met the inclusion criteria and were hospitalized in the Department of Neurology and Medicine at CMH Dhaka were included in the study. Results: The mean age of young patients with ischaemic stroke was 40.1 (SD± 6.6) years (Range 17-45 years). There were 40 (59.7%) male and 27 (40.3%) female with ratio of male to female was 1.5:1. Risk of acute ischaemic stroke was 2.7 times higher in smoker [36 (53.7%) vs 20 (29.9%) OR=2.7, 95% of 01=1.34-5.55, p<0.01] 2.4 times higher in diabetic [23 (34.3%) vs 12 (17.9%), OR=2.4, 95% of 01=1.07-5.35, p<0.05], 2.6 times higher in hypertensive patients [27 (40.3%) vs 14 (20.9%), OR=2.6, 95% of 01=1.19-5.49; p<0.05], 4.2 times higher in patients with atrial fibrillation [11 (16.4%) vs 3 (4.5%)]. The mean BMI of the respondents was 21.8 (SD± 3.3) Kg/M2 in stroke patients of young and was 22.3 (SD 2.9) Kg/M2 in control group (p>0.05). Conclusion: Ischemic stroke in young patients has wider risk factors. Hypertension, diabetes mellitus, smoking and atrial fibrillation are the most common risk factors of acute ischemic stroke in young adults. Early identification of risk factors and proper prevention, treatment and life style modification may reduce the morbidity and mortality in young stroke patients. IAHS Medical Journal Vol 5(2), Dec 2022; 52-57